(untitled) (Upper Saddle River (New Yersey), 1996)
This text provides an introduction to financial decision-making that is rooted both in current financial theory and world economic conditions. It presents ten basic principles (or axioms) of finance in the opening chapter and weaves these concepts throughout the book
Keywords: Business enterprises,Finance,Doanh nghiệp kinh doanh,Tổng công ty; Finance,Corporations,Tài chính,Tài chính